PENGARUH PERSEPSI SISWA TENTANG KEMAMPUAN GURU MENGAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPS TERPADU - Mutmainah Mutmainah; Nurdin Nurdin; Yon Rizal (JEE (Jurnal Edukasi Ekobis), 2013)
Now days, education in Indonesia is faced by the problem of low achievement or student learning outcomes. It is not out of the various factors that affect the learning process in the classroom. such as student’s perception on the teacher's ability in teaching and learning motivation of the students. The purpose of this study was to obtain data on the effect of student’s perception on the teacher's ability in teaching and learning motivation for student of mts nurul iman Sekincau academic year 2012/2013. The population in this study were students of grade VIII first semester MTs Nurul Iman Sekincau with 103 students for threeclasses. By using the T. Yamane formula in probability sampling with a sample obtained 82 peoples, and then performed proportional allocation sampling with samples that taken to be more proportional. The method that used in this study is verification with ex post facto approach. The problem in this study is whether there are influence student’s perception on the teacher's ability for teaching and learning motivation on learning outcomes of IPS Integrated for student grade VIII MTs Nurul Iman Sekincau for first semester on academic year 2012/2013. Based on the analysis of the results for this study shown that : (1). There is a positive and significant effect on the student’s perception on the teacher's ability for teaching at learning outcomes of IPS Integrated for student grade VIII MTs Nurul Iman Sekincau for first semester on academic year 2012/2013. (2). There is a positive and significant of motivation on learning outcomes IPS integrated for student grade VIII MTs Nurul Iman Sekincau for first semester on academic year 2012/2013.       (3). There is a positive and significant effect of effect of student’s perception on the teacher's ability for teaching and learning motivation on learning outcomes of IPS Integrated for student grade VIII MTs Nurul Iman Sekincau for first semester on academic year 2012/2013.Keywords : Students' perceptions about the ability of the teacher in teaching and learning motivation and learning outcomes.